(untitled) (Research, Society and Development, 2021)
The text aims to present the prototype development of a course in the virtual learning environment Moodle, aimed at Technical-Administrative Servers in Education (TAEs) who work at the Federal University of Santa Catarina (UFSC), on public budget, with a focus on aspects of the University’s budget. To achieve this objective, a documentary research was carried out, in which the institution’s budget data, obtained through reports and budget laws, were analyzed. Empirical data were also collected from the TAEs, members of the UFSC staff, through a questionnaire applied with the support of the Google Drive forms tool. The questionnaire aimed to support the creation of the public budget online course for TAEs and, through it, we sought to understand the degree of interest of administrative technical servers in such a course and what, in the perception of these workers, it is important to be addressed. A focus group was also held with the civil servants who work in the Budget Superintendence and in the Accounting and Finance Department at UFSC. We sought to understand what the expectations are regarding what would be addressed in the online course and what these servers perceived as fundamental for teaching in order to qualify the work of the TAEs. As repercussions, it is highlighted that the PACO methodology, created by researchers at the Federal University of São Carlos, served as a guide for the creation of the course prototype. The course was applied and positively evaluated with indication of qualification of work with public budget at UFSC.